1996
DOI: 10.1074/jbc.271.15.9009
|View full text |Cite
|
Sign up to set email alerts
|

Human p300 Protein Is a Coactivator for the Transcription Factor MyoD

Abstract: Human p300 protein is a cellular target of adenoviral E1A oncoprotein and a potential transcriptional coactivator. Both p300 and Rb family protein-binding regions of E1A are required for the repression of muscle gene expression, which is regulated by MyoD family transactivators. This implies that p300 is involved in MyoD-dependent transactivation. We show that the repression of MyoD-mediated E box (MyoD consensus) reporter activity by E1A is correlated with its interaction with p300, indicating that p300 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
304
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(315 citation statements)
references
References 29 publications
11
304
0
Order By: Relevance
“…The observation that promoters activated by CREB, cJun, JunB and cFos can be activated by p300/CBP and repressed by E1A, dependent on the capacity of E1A to bind to p300/CBP, was explained by the binding of E1A to p300/CBP, resulting in inhibition of its coactivator function Lundblad et al, 1995;Lee et al, 1996a). In agreement with these observations it was found that the inhibition of various promoters by E1A could be overcome by overexpression of p300 (Eckner et al, 1994;Yuan et al, 1996;Hasegawa et al, 1997;Puri et al, 1997;Missero et al, 1995;Smits et al, 1996;Lill et al, 1997). We found that under the assay conditions where 12S E1A inhibits the cJun-induced collagenase promoter activity, 12S E1A functionally co-operates with p300 in the activation of the ATF2 Nterminus or the c-jun promoter.…”
Section: Discussionsupporting
confidence: 60%
“…The observation that promoters activated by CREB, cJun, JunB and cFos can be activated by p300/CBP and repressed by E1A, dependent on the capacity of E1A to bind to p300/CBP, was explained by the binding of E1A to p300/CBP, resulting in inhibition of its coactivator function Lundblad et al, 1995;Lee et al, 1996a). In agreement with these observations it was found that the inhibition of various promoters by E1A could be overcome by overexpression of p300 (Eckner et al, 1994;Yuan et al, 1996;Hasegawa et al, 1997;Puri et al, 1997;Missero et al, 1995;Smits et al, 1996;Lill et al, 1997). We found that under the assay conditions where 12S E1A inhibits the cJun-induced collagenase promoter activity, 12S E1A functionally co-operates with p300 in the activation of the ATF2 Nterminus or the c-jun promoter.…”
Section: Discussionsupporting
confidence: 60%
“…Each of these p300 constructs contains at least one of the two activation domains identi®ed in the molecule (Yuan et al, 1996) and was able to enhance MyoDdependent transactivation (Sartorelli et al, 1997). Immunoblot analysis also showed that the amino terminal deletion mutant Cp300 was expressed at similar levels to the full-length protein in transfected NIH3T3 cells (not shown).…”
Section: P300 Augments Transcription Stimulated By Tal1-e12 Heterodimersmentioning
confidence: 94%
“…They have a recognized function as transcriptional coactivators for diverse families of transcription factors, including the nuclear steroid receptors (Chakravarti et al, 1996;Hanstein et al, 1996;Kamei et al, 1996;Yao et al, 1996), and bHLH Mutoh et al, 1998;Qiu et al, 1998;Sartorelli et al, 1997;Yuan et al, 1996), leucine zipper (Bannister and Kouzarides, 1995;Bannister et al, 1995;Chrivia et al, 1993;Mink et al, 1997), and zinc ®nger (Blobel et al, 1998;Lee et al, 1995) proteins. Acting as transcriptional adaptors, they link sequence-speci®c DNA-binding proteins to components of the basal transcriptional machinery (Abraham et al, 1993;Kee et al, 1996;Nakajima et al, 1997) and to proteins with histone acetyltransferase activity (Yang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of p300/CBP by E1A inhibits the transcription of the p21 CIP1/WAF1 induced by DNA damage (Steegenga et al, 1996;Somasundaram and el-Deiry, 1997), transforming growth factor-b (TGF-b) (Datto et al, 1997), keratinocytes and myoblasts terminal differentiation (Missero et al, 1995;Cenciarelli et al, 1999). In the cases above mentioned, the transcription of p21 CIP1/WAF1 depends either on p53 (Vogelstein et al, 2000) or on differentiation-specific factors like MyoD (Cenciarelli et al, 1999), RB family proteins and small DNA virus oncoproteins A Felsani et al and p300/CBP is the transcriptional coactivator both of p53 (Avantaggiati et al, 1997;Lill et al, 1997) and MyoD (Eckner et al, 1996;Yuan et al, 1996). The interaction of E1A N-terminal region with p400, a member of SWI2/SNF2 chromatin remodeling complex (Fuchs et al, 2001), may also deregulate the p53-p21 CIP1/WAF1 pathway, leading to a downregulation of p21 CIP1/WAF1 (Chan et al, 2005).…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%